KORELASI ANTARA MINAT BACA DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR TEMATIK - Tyastuti Aditya; Kartono Kartono; Syambasril Syambasril (Universitas Tanjungpura, 2020)
Abstract This study aimed to analyze the correlation between reading interest and learning motivation with learning outcomes of V grade student at SDN 46 Sungai Raya. The research method used was descriptive research. The form of this research was correlation study. The population in this study were 25 students of grade V SDN 46 Sungai Raya. The sample in this study used a total sample 25 students grade V SDN 46 Sungai Raya. The result showed that reading interest was 78,656%, learning motivation was 78,5%, and learning outcomes obtained an average of 79,44. Statistical calculations were done by the product moment correlation formula that reading interest and learning outcomes obtained ???????????????????????? 0,659, learning motivation and learning outcomes obtained ???????????????????????? 0,657, reading interest and learning motivation obtained ???????????????????????? 0,71. Reading interest and learning motivation with learning outcomes used the multiple correlation formula obtained ????????????1????2 0,71. It was categorized as a strong relationship with ???????????????????????? 11,18 and ???????????????????????? ???? = 5% of 3,39 wich means ????ℎ???????????????????? (11,18) > ???????????????????????? (3,39), then Ha is accepted. So, it can be concluded that there is a relationship between reading interest and learning motivation with learning outcomes in thematic learning of V grade students at SDN 46 Sungai Raya. Keywords: Correlation, Learning Motivation, Learning Outcomes, Reading Interest